A framework for sentiment analysis: a data-driven approach - Islam, Md. Jahedul; Sarker, Tonmoy; Shuvo, Md. Shubiour; Hossen, Md. Robin; Ahmedh, Minhaz Uddin (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.